High-sensitivity high-resolution X-ray imaging with soft-sintered metal halide perovskites - Deumel, Sarah; Van Breemen, Albert; Gelinck, Gerwin; Peeters, Bart; Maas, Joris; Verbeek, Roy; Shanmugam, Santhosh; Akkerman, Hylke; Meulenkamp, Eric; Huerdler, Judith E.; Acharya, Manognya; Garcia-Batlle, Marise; et al. (Nature Electronics, 2021)
To realize the potential of artificial intelligence in medical imaging, improvements in imaging capabilities are required, as well as advances in computing power and algorithms. Hybrid inorganic–organic metal halide perovskites, such as methylammonium lead triiodide (MAPbI3), offer strong X-ray absorption, high carrier mobilities (µ) and long carrier lifetimes (τ), and they are promising materials for use in X-ray imaging. However, their incorporation into pixelated sensing arrays remains challenging. Here we show that X-ray flat-panel detector arrays based on microcrystalline MAPbI3 can be created using a two-step manufacturing process. Our approach is based on the mechanical soft sintering of a freestanding absorber layer and the subsequent integration of this layer on a pixelated backplane. Freestanding microcrystalline MAPbI3 wafers exhibit a sensitivity of 9,300 µC Gyair–1 cm–2 with a μτ product of 4 × 10–4 cm2 V–1, and the resulting X-ray imaging detector, which has 508 pixels per inch, combines a high spatial resolution of 6 line pairs per millimetre with a low detection limit of 0.22 nGyair per frame.
CRIS-Team Scopus Importer:2021-10-01